A method for producing an alumina ceramic for an electrostatic chuck
Patent Information
- Application Number
- CN202511478286.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-16
- Publication Date
- 2026-10-13
AI Technical Summary
片层坯体的下表面进行保温,所述加热温度为85-95℃,实现得到丝印用第一片层坯体的上表面部分溶剂挥发,上表面干燥,从而有利于丝印的钨浆与第一片层坯体结合强度高,从而避免了制备的静电卡盘用氧化铝陶瓷的制备法的电极层在使用过程中出现脱落的问题;同时实现第一片层坯体的下表面,甚至周边的溶剂不挥发,从而既有利于避免第一片层坯体的下表面变形,同时有利于第一片层的下表面与第二片层坯体叠加结合时,结合强度高,且结合处结构均匀;
Abstract
Description
Technical Field
[0001] This invention relates to the field of alumina ceramic preparation technology, and in particular to a method for preparing alumina ceramic for electrostatic chucks. Background Technology
[0002] An electrostatic chuck is a key component that uses electrostatic adsorption to hold wafers within semiconductor processing equipment such as lithography machines, etching machines, and vapor deposition equipment. Compared to traditional mechanical clamping and vacuum adsorption, electrostatic chucks offer advantages such as uniform adsorption force, no mechanical damage, and precise temperature control, making them particularly suitable for semiconductor manufacturing environments with extremely high precision and cleanliness requirements. An electrostatic chuck mainly consists of a ceramic disk and a metal base. Therefore, the ceramic disk is a core precision functional ceramic component of the electrostatic chuck (with extremely high technological content). The ceramic disk contains a dielectric layer and an electrode layer, and is often made by co-firing multiple layers of ceramic and metal. It is not only the physical support platform for the wafer but also the core component for achieving precise thermal management, stable electrostatic adsorption, and ensuring process uniformity and yield. Its material properties, processing accuracy, and reliability determine the lifespan and process stability of the electrostatic chuck.
[0003] To prepare ceramic disks using alumina ceramics, the alumina ceramics need to be large in size, have a smooth and flat surface, be highly dense, have small grains, and have an electrode layer inside. Therefore, how to prepare an alumina ceramic for electrostatic chucks, with fine internal grains, narrow grain size distribution, uniform overall structure, high density, and an internal electrode layer, has become a pressing problem to be solved in this field. Summary of the Invention
[0004] To solve the above-mentioned technical problems, the present invention provides a method for preparing alumina ceramic for electrostatic chucks, which achieves fine internal grains, narrow distribution and overall uniformity, high degree of densification, and an internal electrode layer.
[0005] This invention provides a method for preparing alumina ceramic for electrostatic chucks, comprising the following: step: Preparation of mixed additive powder; The additive powders include MgO powder, Y2O3 powder, TiO2 powder, SiO2 powder, SiC powder, and ZrO2 powder; Mixed additive powder is mixed with fine-grained α-Al2O3 powder to prepare mixed raw materials; Prepare the first mixed solution; Then, the binder and mixed raw materials are added to the first mixed solution to prepare the primary slurry; The primary slurry is degassed to obtain a casting slurry; The casting slurry is cast to obtain a sheet preform; the sheet preform includes... The first layer of blank and several second layer blanks; After preprocessing the first sheet blank, a first sheet blank for screen printing is obtained; An electrode layer is attached to the surface of the first sheet blank for screen printing using screen printing paste. A composite electrode sheet preform was obtained; The composite electrode sheet blank and several second sheet blanks are laminated and hot-pressed. The process involves molding to obtain an alumina ceramic blank for an electrostatic chuck. Alumina ceramic for electrostatic chucks is obtained by debinding and sintering an alumina ceramic blank. The prepared electrostatic chuck uses alumina ceramic with a surface roughness Ra≤0.2μm, no delamination or microcrack defects, and a dielectric constant ≥14, volume resistivity ≥1*1014Ω·cm, and bending strength ≥550Mpa. Preferably, the composite electrode sheet blank is combined with 5-9 second sheet blanks; more preferably, the composite electrode sheet blank is laminated and warm-pressed in a mold.
[0006] Compared with the prior art, the present invention has the following beneficial effects: by using the auxiliary powder, which includes MgO powder, Y2O3 powder, TiO2 powder, SiO2 powder, SiC powder, and ZrO2 powder, the MgO powder fills the grain boundary defects of Al2O3, which helps to suppress carrier migration, improve volume resistivity, and ensure the stability and reliability of electrostatic adsorption; and forms a solid solution with Al2O3, which optimizes dielectric properties and enhances electric field stability. The synergistic effect of Y2O3 powder and TiO2 powder helps to reduce the sintering temperature, promote low-temperature densification sintering, inhibit abnormal grain growth, and obtain a fine and uniform microstructure. This is beneficial to achieve fine and dense internal grains in alumina ceramics, thereby improving the strength, hardness and wear resistance of the material. SiO2 powder helps to refine surface grains, reduce surface roughness, improve adsorption effect, reduce contact thermal resistance and enhance anti-pollution ability. SiC powder helps to hinder crack propagation through a dispersion toughening mechanism, thereby further improving the fracture toughness and thermal shock resistance of the material; ZrO2, with its phase transformation toughening effect and matching thermal expansion coefficient, further helps to alleviate thermal stress and prevent the ceramic disk from cracking during thermal cycling.
[0007] A sheet-like preform is obtained by casting with the aforementioned casting slurry; thus achieving internal [removal / capacity] of the sheet-like preform. The structure is uniform, and the particle size distribution of the ceramic powder is uniform. The lamellar blank includes a first lamellar blank and a plurality of second lamellar blanks, through An electrode layer is attached to the surface of the first sheet blank for screen printing using screen printing paste to obtain a composite electrode sheet blank, thereby realizing that the prepared alumina ceramic has an electrode layer inside. By preprocessing the first sheet blank, a first sheet blank for screen printing is obtained. The body achieves uniform bonding between the first layer blank and the surface-attached electrode layer, while avoiding the problem of low bonding strength when the first layer blank is bonded to the second layer blank, and avoiding the problem of easy cracking at the bonding point. By stacking the composite electrode sheet blank with several second sheet blanks at a temperature... Press molding yields an alumina ceramic blank for electrostatic chucks. The internal structure of the alumina ceramic blank for electrostatic chucks is uniform, and the internal powder particles are of uniform size. This further facilitates the achievement of a fine-grained alumina ceramic with a uniform internal structure, small grain size, and uniform grain size distribution.
[0008] Furthermore, the process of preparing the mixed additive powder includes the following steps: MgO powder, Y2O3 powder, TiO2 powder, SiO2 powder, SiC powder, and ZrO2 powder are added to a ball mill in a mass ratio of (1-3):(0.2-1):(0.2-1):(1-2):(0.5-2):(0.5-2) and mixed in the ball mill to obtain the mixed additive powder. The particle size of the mixed additive powder is 0.5-1μm.
[0009] Furthermore, the mass ratio of α-Al2O3 powder to mixed additive powder is (95-99): (3.4-11); The particle size of the α-Al2O3 powder is 0.5-1μm.
[0010] The advantage of the previous step is that it results in fine particle size of the added mixed additive powder and α-Al2O3 powder, which is beneficial for the preparation of alumina ceramic for electrostatic chucks with small internal grain size.
[0011] Furthermore, the process of preparing the mixed raw materials includes the following steps: α-Al2O3 powder and polyvinylpyrrolidone are mixed in a ball mill to prepare a first-attached material grinding ball, which is coated with α-Al2O3 powder. Mixing the mixed additive powder and the first attached material grinding balls in a ball mill to prepare the second attached material grinding balls, which are coated with α-Al2O3 powder and mixed additive powder; The material attached to the second grinding ball is detached from the grinding ball, and then ground. The mixed raw materials are obtained.
[0012] The beneficial effect of the previous step is that the first adhering material grinding ball is coated with α-Al2O3 powder, and then the mixed additive powder and the first adhering material grinding ball are mixed in a ball mill to prepare the second adhering material grinding ball. The second adhering material grinding ball is coated with α-Al2O3 powder and mixed additive powder, so that the nano alumina powder and inorganic powder are mixed evenly and there is no problem of agglomeration. By detaching the material attached to the second-attached grinding ball from the grinding ball, and then grinding... The mixed raw materials are obtained, which separates the uniformly mixed α-Al2O3 powder and mixed additive powder from the grinding balls. At the same time, the powder particles of the mixed raw materials are of moderate size, which avoids the problem of agglomeration when the mixed powder is used to prepare casting slurry. This is conducive to the preparation of alumina ceramic for electrostatic chuck with small and uniform grain size.
[0013] Furthermore, the process of preparing the first coated material grinding ball also includes the following steps: The polyvinylpyrrolidone was added to a ball mill for grinding, and the grinding process was carried out. The material temperature rises to 130-150℃; Then, while grinding, the temperature is lowered to room temperature, and polyvinylpyrrolidone is applied to the surface of the grinding ball; Then add α-Al2O3 powder and grind at room temperature for 10-50 min; Then, while grinding, heat the material to 130-135℃ at a rate of 2-5℃ / min, and grind it at 130-135℃ for 10-20 minutes. Then, while grinding, the temperature is lowered until the first attached material grinding ball is obtained after cooling to room temperature. Preferably, the diameter of the grinding ball is 1.0-2.0 mm, and the volume ratio of the grinding ball to nano-alumina is (2-4):1.
[0014] The beneficial effect of the previous step is that by adding the polyvinylpyrrolidone to the spheres The material is ground in a grinding equipment, and the temperature of the material is raised to 130-150℃ during grinding to achieve liquefaction of polyvinylpyrrolidone and uniform contact with the grinding balls. Then, α-Al2O3 powder is added and ground at room temperature for 10-50 minutes to achieve uniform contact between α-Al2O3 powder and the grinding balls with attached polyvinylpyrrolidone. By grinding and heating simultaneously, the material temperature is raised to 130-135℃ at a rate of 2-5℃ / min. Grinding is then carried out at 130-135℃ for 10-20 minutes, which slowly melts the polyvinylpyrrolidone on the surface of the grinding ball and evenly adheres the nano-alumina powder to the surface of the grinding ball, thus obtaining grinding balls with α-Al2O3 powder attached. The diameter of the grinding ball is 1.0-2.0 mm, and the volume ratio of the grinding ball to nano-alumina is (2-4):1, which is beneficial to achieve uniform adhesion of nano-alumina to the surface of the grinding ball.
[0015] Furthermore, the process of preparing the second attached material grinding balls includes the following steps: The mixed additive powder, polyethylene glycol, and the first adhering material grinding balls are placed in a ball mill, and the temperature is increased while the ball mill is being milled, raising the material temperature to 64-68℃. After ball milling at 64-68℃ for 10-20 minutes, the mixture is cooled to room temperature to obtain... Second attached material grinding balls.
[0016] and / or The process of removing the material adhering to the second-attached grinding ball from the grinding ball includes: The following steps: The second type of adhering material grinding balls are placed in a ball mill, and the mill is heated while grinding. Heat to 250-260℃; grind at 250-260℃ for 10-20 minutes; Then, while ball milling, the temperature is reduced, and grinding continues for 10-20 minutes after the temperature is reduced to room temperature. The alumina powder and inorganic powder attached to the grinding balls detach from the grinding balls, resulting in a mixture. and / or The particle size of the second mixture is D50 = 3.0-5.0 μm.
[0017] The beneficial effect of the previous step is that the mixed additive powder, polyethylene glycol, and the first attached material grinding balls are milled in a ball mill while the temperature is increased to 64-68℃, so that the polyethylene glycol melts while the polyvinylpyrrolidone on the surface of the grinding balls does not melt. By ball milling at 64-68℃ for 10-20 minutes, followed by cooling to room temperature, the desired effect is achieved. The mixed additive powder is attached to the first attachment material grinding ball by melting polyethylene glycol, thus obtaining the second attachment material grinding ball.
[0018] By placing the second attached material grinding balls into a ball mill, and simultaneously grinding and heating them, Heating to 250-260℃; grinding at 250-260℃ for 10-20 minutes, the polyethylene glycol and polyvinylpyrrolidone attached to the grinding balls of the second adhering material melt and volatilize, thereby allowing the mixed powder after the mixed additive powder and α-Al2O3 powder are evenly mixed to detach from the surface of the grinding balls, achieving uniform mixing of the mixed additive powder and α-Al2O3 powder, and avoiding the problem of agglomeration of the mixed additive powder or α-Al2O3 powder; By using a second mixture with a particle size of D50 = 3.0-5.0 μm, the second mixture is avoided. Agglomeration occurs during the preparation of primary slurry.
[0019] Furthermore, the process for preparing the first mixed solution includes: Mix toluene and isopropanol and stir. Then add dibutyl phthalate, polyethylene glycol, and polyvinyl butyral and continue stirring to obtain the first mixed solution; and / or The process of preparing the primary slurry includes: The mixed raw materials are added to the first mixed solution and stirred for 2.5-3.0 hours, then allowed to stand for 5.5-6.0 hours, and then stirred again for 0.5-1.5 hours to obtain the primary slurry.
[0020] and / or The toluene, isopropanol, dibutyl phthalate, polyethylene glycol, and polyvinyl alcohol mentioned above. The mass ratio of butyral is (60-70):(20-30):(5-10):(20-30):(1-10); The mass ratio of the first mixed solution to the mixed raw materials is (1.8-2.5):1.
[0021] The beneficial effect of the previous step is that, through the aforementioned toluene, isopropanol, and phthalic acid... The mass ratio of dibutyl phthalate, polyethylene glycol, and polyvinyl butyral is (60-70):(20-30):(5-10):(20-30):(1-10); the mass ratio of the first mixed solution to the mixed raw materials is (1.8-2.5):1, which ensures that the subsequent casting slurry has good flowability and is controllable, thereby achieving high precision in controlling the shape and size of each sheet blank; at the same time, it ensures that the materials in the obtained primary slurry are evenly dispersed, and the mixed raw materials are fully dispersed in the primary slurry, which is beneficial to the subsequent aging process. The particle size of the fine α-Al2O3 powder and the particle size of the additive powder in the mixed raw materials are reduced, and are basically consistent with the particle size of the fine α-Al2O3 powder and the particle size of the additive powder, which are relatively small. This is beneficial to the preparation of alumina ceramics for electrostatic chucks with small and uniform grain size.
[0022] The primary slurry is added to a ball mill and ball-milled for 20-25 hours, then filtered. Further, the particle size of the mixed raw materials is basically the same as that of the raw material and auxiliary powder, both being relatively small, and the mixture is uniform.
[0023] Furthermore, the process of degassing the primary slurry to obtain the casting slurry includes the following steps: The primary slurry is added to a ball mill and milled for 20-25 hours, then filtered with a filter screen of 250-400 mesh. The filtered primary slurry is fed into a degassing device using nitrogen gas to process the primary slurry. Heating to 85-95℃ while simultaneously applying a vacuum, the resulting slurry is obtained when the viscosity reaches 2-6 Pa·s.
[0024] The mesh size of the filter screen for primary slurry filtration is 250-400 mesh.
[0025] Building upon the beneficial effects of the previous step, the filtered primary slurry is fed into a degassing device using nitrogen gas. The primary slurry is heated to 85-95℃ while being vacuumed. When the viscosity reaches 2-6 Pa·s, a casting slurry is obtained, thus removing excess solvent. This ensures good flowability of the casting slurry while reducing the difficulty of solvent removal during casting. Simultaneously, heating the primary slurry to 85-95℃ melts the polyethylene glycol and softens the polyvinyl butyral, preventing excessive viscosity changes in the casting slurry during subsequent casting and avoiding uneven sheet thickness caused by excessive fluidity.
[0026] Furthermore, the process of casting the slurry to obtain a sheet preform includes the following steps: The temperature of the casting slurry is 165-175℃ when it is cast through the casting equipment. The casting speed is 10-300 mm / min, and the scraper is kept away from the conveying sheet blank during the casting process. The height of the cast strip is 10-30mm; and / or The pretreatment process of the first sheet blank includes the following steps: The upper surface of the first sheet blank is heated, and during the heating process, the first sheet blank is heated. The lower surface of the blank is kept warm. The heating temperature is 85-95℃. After heating for 15-30 minutes, the first layer blank for screen printing is obtained. and / or The electrode layer is attached to the surface of the first sheet blank for screen printing using screen printing paste. The process includes the following steps: The tungsten paste is repeatedly screen-printed onto the surface of the first sheet blank for screen printing. A composite electrode sheet preform was obtained; Each screen printing layer is 10-15mm thick, followed by drying at 60°C. Dry at 80℃ for 15-20 minutes, then proceed with the next screen printing after drying. Preferably, the composite electrode sheet preform is placed in an environment with a humidity of 20%-40%. Let it stand for 30-60 minutes, and then stack it with several second-layer blanks for warm pressing.
[0027] Preferably, the tungsten paste comprises tungsten paste in a mass ratio of (85-90):(1-5):(6-12). Tungsten powder, glass powder, and organic carrier.
[0028] The advantage of the previous step is that when the casting slurry is cast through the casting equipment at a temperature of 165-175℃, the polyvinyl butyral is completely melted, resulting in a uniform and fine casting slurry. By using a casting speed of 1-300 mm / min and keeping the height of the scraper from the casting belt conveying the sheet blank at 0.3-0.6 mm during the casting process, a sheet blank thickness of 0.3-0.6 mm can be achieved.
[0029] By heating the upper surface of the first sheet blank, during the heating process, the first... The lower surface of the sheet blank is kept warm at a temperature of 85-95℃, which allows some of the solvent on the upper surface of the first sheet blank for screen printing to evaporate and the upper surface to dry. This promotes a high bonding strength between the tungsten paste for screen printing and the first sheet blank, thus avoiding the problem of electrode layer detachment during use in the preparation method of alumina ceramic for electrostatic chucks. At the same time, it prevents the solvent from evaporating from the lower surface and even the surrounding area of the first sheet blank, which helps to avoid deformation of the lower surface of the first sheet blank and also promotes high bonding strength and uniform structure at the bonding joint when the lower surface of the first sheet blank is superimposed on the second sheet blank. The tungsten paste is repeatedly screen-printed onto the surface of the first sheet blank for screen printing. A composite electrode sheet blank is obtained; the thickness of each screen printing is 10-15 mm, and after screen printing, it is dried at a temperature of 60-80℃ for 15-20 min. After drying, the next screen printing is carried out; the electrode layer with a thickness of 40 mm or more is prepared, and the electrode layer structure is uniform and the bonding strength between the electrode layer and the ceramic structure is high, which further helps to avoid the problem of electrode layer falling off during use.
[0030] By placing the composite electrode sheet preform in an environment with a humidity of 20%-40% and allowing it to stand... After 30-60 minutes, it is then laminated and warm-pressed with several second-layer blanks. This avoids the problem of deformation on the side of the composite electrode blank with the electrode layer after the first-layer blank has been heated and some solvent has evaporated. It also avoids the problem of low bonding strength when the side of the composite electrode blank with the electrode layer is bonded to the second-layer blank.
[0031] Furthermore, the pressure during the warm isostatic pressing process is 5-10 MPa, the temperature is 85-100℃, and the holding time is 50-60 min; The process of debinding and sintering alumina ceramic preforms for electrostatic chucks includes the following steps: Debinding and sintering are carried out under nitrogen and hydrogen atmospheres; A mixture of nitrogen and hydrogen is introduced; the hydrogen flow rate is 3.8-4.2 L / min, and the nitrogen flow rate is 4.5-5.5 L / min; the hydrogen is wet hydrogen with a dew point temperature of 30-40℃. The electrostatic chuck is placed on a flat and smooth alumina sintering plate and then placed in an integrated debinding and sintering furnace. The temperature is raised from room temperature to 110-120℃ at a rate of 1-2℃ / min. The heating rate is 0.3-0.5℃ / min when the temperature is increased from 110-120℃ to 250-260℃; and 0.1-0.2℃ / min when the temperature is increased from 250-260℃ to 700-720℃. Keep warm at 700-720℃ for 8-10 hours; The temperature is raised to 1200-1220℃ at a rate of 1.5-2.0℃ / min; at 1200-1220℃ Hold at this temperature for 120-150 minutes; raise the temperature from 1200-1220℃ to 1560-1580℃ at a rate of 2.5-3.0℃ / min; and hold at 1560-1580℃ for 120-150 minutes. and / or Then, cooling is performed, and the cooling process includes: The temperature is reduced from 1560-1580℃ to 1350-1300℃ at a rate of -3 to -4℃ / min. Replace the introduced hydrogen with dry hydrogen, then cool from 1350-1300℃ to 500-600℃ at a rate of -4 to -5℃ / min; cool from 500-600℃ to room temperature along with the furnace.
[0032] The beneficial effect of the previous step is that, through the isostatic pressing process with a pressure of 5-10 MPa and a temperature of 85-100℃, held for 50-60 minutes, the viscosity of polyethylene glycol increases, the bonding strength between each layer of the preform is high, and polyvinyl butyral softens without melting. Under this pressure, isostatic pressing further achieves a uniform internal structure of the alumina ceramic preform for electrostatic chucks. By rapidly heating the alumina ceramic preform for the electrostatic chuck from room temperature to 100-110℃ at a rate of 1-2℃ / min, residual small-molecule volatiles are quickly volatilized, forming small-pore channels. A slower heating rate, from 100-110℃ to 250-260℃ at a rate of 0.3-0.5℃ / min, allows for the slow decomposition of larger molecular weight volatiles, such as polyethylene glycol and polyvinyl butyral. Further slow heating, from 250-260℃ to 720℃ at a rate of 0.1-0.2℃ / min, allows the volatiles remaining after the decomposition of large molecules to evaporate through the channels formed by the volatilization of smaller molecules, thus preventing cracking of the alumina ceramic preform for the electrostatic chuck. The temperature is increased from 700-720℃ to 1200-1220℃ at a rate of 1.5-2.0℃ / min. Hold at 1200-1220℃ for 120-150 min, then hold at 1200-1220℃ for 120-150 min; increase the temperature from 1200-1220℃ to 1560-1580℃ at a rate of 2.5-3.0℃ / min. This increased heating rate helps to avoid the problem of increased grain size in the alumina ceramic used in electrostatic chucks after sintering. The temperature was lowered from 1560-1580℃ to 1350-1300℃ at a rate of -3 to -4℃. The cooling rate of -4.5 to -5.5℃ / min avoids the problem of grain enlargement in alumina ceramics used in electrostatic chucks caused by slow cooling, while also helping to avoid excessive internal stress during cooling. By replacing the introduced hydrogen with dry hydrogen and then cooling from 1350-1300℃ to 500-600℃ at a rate of -4.5 to -5.5℃ / min, the cooling rate is further improved, thus avoiding the problem of grain enlargement in alumina ceramics used in electrostatic chucks caused by slow cooling. Cooling from 500-600℃ to room temperature with the furnace further helps to release the internal stress of alumina ceramics used in electrostatic chucks. Detailed Implementation
[0033] To better understand the technical solution of the present invention, the present invention will be further described below with reference to specific embodiments.
[0034] Example 1: This embodiment provides a method for preparing alumina ceramic for electrostatic chucks, comprising the following steps: preparing mixed additive powder; The additive powder includes MgO powder, Y2O3 powder, TiO2 powder, SiO2 powder, and SiC. Powder, ZrO2 powder; the process of preparing mixed additive powder includes the following steps: MgO powder, Y2O3 powder, TiO2 powder, SiO2 powder, SiC powder, and ZrO2 powder are added to a ball mill in a mass ratio of 2:0.6:0.6:1.5:1.3:1.3 and mixed in the ball mill to obtain the mixed additive powder; the particle size of the mixed additive powder is 0.5-1μm.
[0035] A mixed raw material was prepared by mixing the mixed additive powder with fine-grained α-Al₂O₃ powder; α-Al₂O₃ The mass ratio of the powder to the mixed additive powder is 97:7.2; the particle size of the α-Al2O3 powder is 0.5-1μm.
[0036] The process of preparing the mixed raw materials includes the following steps: α-Al2O3 powder and polyvinylpyrrolidone are mixed in a ball mill to prepare a first-attached material grinding ball, which is coated with α-Al2O3 powder. Mixing the mixed additive powder and the first attached material grinding balls in a ball mill to prepare the second attached material grinding balls, which are coated with α-Al2O3 powder and mixed additive powder; The material attached to the second grinding ball is detached from the grinding ball, and then ground. The mixed raw materials are obtained.
[0037] The process of preparing the first coated material grinding balls also includes the following steps: The polyvinylpyrrolidone was added to a ball mill for grinding, and the grinding process was carried out. The material temperature rises to 140℃; Then, while grinding, the temperature is lowered to room temperature, and polyvinylpyrrolidone is applied to the surface of the grinding ball; Then add α-Al2O3 powder and grind at room temperature for 30 minutes; Then, while grinding, heat the material and raise the temperature to 132℃ at a rate of 3.5℃ / min. Grind the material at 132℃ for 15 minutes. Then, while grinding, the temperature is lowered until the first attached material grinding ball is obtained after cooling to room temperature. The grinding ball has a diameter of 1.5 mm, and the volume ratio of the grinding ball to nano-alumina is 3:1.
[0038] The process of preparing the second-attached material grinding balls includes the following steps: The mixed additive powder, polyethylene glycol, and the first adhering material grinding balls are placed in a ball mill while the temperature is increased to 66°C. After ball milling at 66℃ for 15 minutes, the mixture was cooled to room temperature to obtain the second deposit. Grinding balls for materials.
[0039] The process of removing the material adhering to the second-attached grinding ball from the grinding ball includes: The following steps: The second type of adhering material grinding balls are placed in a ball mill, and the mill is heated while grinding. Heat to 255℃; grind at 255℃ for 15 minutes; Then, while ball milling, the temperature is reduced, and grinding continues for 15 minutes after the temperature is reduced to room temperature. The alumina powder and inorganic powder attached to the grinding balls detach from the grinding balls, resulting in a mixture. The particle size of the second mixture is D50 = 4.0 μm.
[0040] Preparation of the first mixed solution; the process of preparing the first mixed solution includes: Mix toluene and isopropanol and stir. Then add dibutyl phthalate, polyethylene glycol, and polyvinyl butyral and continue stirring to obtain the first mixed solution; The toluene, isopropanol, dibutyl phthalate, polyethylene glycol, and polyvinyl alcohol mentioned above. The mass ratio of butyral is 65:25:8:25:6; The mass ratio of the first mixed solution to the mixed raw materials is 2.1:1.
[0041] Then, the binder and mixed raw materials are added to the first mixed solution to prepare the primary slurry; the process of preparing the primary slurry includes: The mixed raw materials are added to the first mixed solution and stirred for 2.8 hours, then allowed to stand and age for 5.7 hours, and then stirred again for 1 hour to obtain the primary slurry.
[0042] The primary slurry is degassed to obtain a casting slurry, specifically including the following steps: The primary slurry is added to a ball mill and milled for 20-25 hours, then filtered. Mesh number: 325 mesh; The filtered primary slurry is fed into a degassing device using nitrogen gas to process the primary slurry. Heating to 90℃ while simultaneously applying a vacuum, the slurry is obtained when the viscosity reaches 4 Pa·s.
[0043] The casting slurry is cast to obtain a sheet preform; the sheet preform includes a first The process of obtaining the sheet-like preform by casting a casting slurry includes the following steps: (The process involves casting a sheet-like preform with a layered preform and several second sheet-like preforms.) The temperature of the casting slurry is 170℃ when it is cast through the casting equipment. The casting speed is 155 mm / min, and the scraper moves away from the conveying sheet blank during the casting process. The height of the cast tape is 20mm.
[0044] After preprocessing the first sheet blank, the first sheet blank for screen printing is obtained. The pretreatment process of the first layered blank includes the following steps: The upper surface of the first sheet blank is heated, and during the heating process, the first sheet blank is heated. The lower surface of the blank is kept warm. The heating temperature is 90°C. After heating for 22 minutes, the first layer blank for screen printing is obtained. An electrode layer is attached to the surface of the first sheet blank for screen printing using screen printing paste, thereby obtaining... Composite electrode sheet preform; the process of attaching an electrode layer to the surface of the first sheet preform for screen printing using screen printing paste includes the following steps: The tungsten paste is repeatedly screen-printed onto the surface of the first sheet blank for screen printing to obtain... Composite electrode sheet preform; Each screen printing layer is 12mm thick, and after screen printing, it is dried at a temperature of 70℃. The drying time is 18 minutes, and the next screen printing is performed after drying; the tungsten paste includes tungsten powder, glass powder and organic carrier in a mass ratio of 88:3:9.
[0045] The composite electrode sheet blank and several second sheet blanks are laminated and hot-pressed. The process involves molding to obtain an alumina ceramic blank for an electrostatic chuck; the composite electrode sheet blank is then combined with seven second sheet blanks; the isostatic pressing process is carried out at a pressure of 8 MPa and a temperature of 92°C for 55 min. Alumina ceramic for electrostatic chucks is obtained by debinding and sintering an alumina ceramic blank. The process of debinding and sintering alumina ceramic preforms for electrostatic chucks includes the following steps: Debinding and sintering are carried out under a nitrogen and hydrogen atmosphere; a mixture of nitrogen and hydrogen is introduced. The gas flow rate is 4 L / min for hydrogen and 5 L / min for nitrogen; the hydrogen is wet hydrogen with a dew point temperature of 35°C. The electrostatic chuck is placed on a flat and smooth alumina sintering plate and then placed in an integrated debinding and sintering furnace. The temperature is raised from room temperature to 115°C at a rate of 1.5°C / min. The temperature was increased from 115℃ to 255℃ at a rate of 0.4℃ / min; the temperature was increased from 255℃ to... 710℃, heating rate of 0.15℃ / min; hold at 710℃ for 9 hours; The temperature was raised to 1210℃ at a rate of 1.8℃ / min; and held at 1210℃ for 135 min. The temperature was increased from 1210℃ to 1570℃ at a rate of 2.8℃ / min; and held at 1570℃ for 135 min. Then, cooling is performed, and the cooling process includes: The temperature was reduced from 1570℃ to 1325℃ at a rate of -3.5℃ / min. The introduced hydrogen gas was replaced with dry hydrogen, and then the temperature was lowered from 1325℃ to 550℃ at a rate of -4.5℃ / min; the temperature was then lowered from 550℃ to room temperature along with the furnace.
[0046] The prepared electrostatic chuck uses alumina ceramic with a surface roughness Ra ≤ 0.19 μm, no delamination or microcrack defects, and a dielectric constant of 15 and a volume resistivity of 1*10. 15 Ω·cm, flexural strength is 560Mpa.
[0047] Example 2: The contents that are the same as in Example 1 will not be repeated here; this embodiment is different from Example 1. The same scheme is as follows: A method for preparing alumina ceramic for electrostatic chucks further includes placing the composite electrode sheet blank in an environment with a humidity of 30% and letting it stand for 45 minutes, and then stacking and warm pressing it with several second sheet blanks.
[0048] The technical solution different from Example 1 further includes: adding MgO powder, Y2O3 powder, TiO2 powder, SiO2 powder, SiC powder, and ZrO2 powder into a ball mill in a mass ratio of 2.8:0.9:0.9:1.8:1.8:1.8, and mixing them in the ball mill to obtain the mixed additive powder.
[0049] The mass ratio of α-Al2O3 powder to mixed additive powder is 98:10.
[0050] The process of preparing the first coated material grinding balls also includes the following steps: The polyvinylpyrrolidone was added to a ball mill for grinding, and the grinding process was carried out. The material temperature rose to 148℃; Then add α-Al2O3 powder and grind at room temperature for 46 min; Then, while grinding, heat the material and raise the temperature to 134℃ at a rate of 4.8℃ / min. Grind the material at 134℃ for 18 minutes. The grinding ball has a diameter of 1.8 mm, and the volume ratio of the grinding ball to nano-alumina is 3.6:1.
[0051] The process of preparing the second-attached material grinding balls includes the following steps: The mixed additive powder, polyethylene glycol, and the first adhering material grinding balls are placed in a ball mill while the temperature is increased to 67°C. After ball milling at 67℃ for 19 minutes, the mixture was cooled to room temperature to obtain the second deposit. Grinding balls for materials.
[0052] The process of removing the material adhering to the second-attached grinding ball from the grinding ball includes: Next steps: The second type of adhering material grinding balls are placed in a ball mill, and the mill is heated while grinding. Heat to 258℃; grind at 258℃ for 18 minutes; Then, while ball milling, the temperature is lowered, and grinding continues for 12 minutes after the temperature is lowered to room temperature. The alumina powder and inorganic powder attached to the grinding balls detach from the grinding balls, resulting in a mixture. The particle size of the second mixture is D50 = 4.8 μm.
[0053] The toluene, isopropanol, dibutyl phthalate, polyethylene glycol, and polyvinyl alcohol mentioned above. The mass ratio of butyral is 68:28:9:28:9; The mass ratio of the first mixed solution to the mixed raw materials is 2.4:1.
[0054] The mixed raw materials are added to the first mixed solution and stirred for 2.8 hours, then allowed to stand for 5.8 hours, and then stirred again for 1.3 hours to obtain the primary slurry.
[0055] The primary slurry was added to a ball mill and ball-milled for 23 hours, then filtered. The mesh count is 380. The filtered primary slurry is fed into a degassing device using nitrogen gas to process the primary slurry. Heating to 92℃ while simultaneously applying a vacuum, the slurry is obtained when the viscosity reaches 5 Pa·s.
[0056] The temperature of the casting slurry is 173℃ when it is cast through the casting equipment. The casting speed is 260 mm / min, and the scraper moves away from the conveying sheet blank during the casting process. The height of the belt is 15mm.
[0057] The upper surface of the first sheet blank is heated, and during the heating process, the first sheet blank is heated. The lower surface of the blank is kept warm. The heating temperature is 85-95℃. After heating for 15-30 minutes, the first layer blank for screen printing is obtained. Each screen printing layer is 14mm thick, followed by drying at 78℃. The drying time is 18 minutes, and the next screen printing is performed after drying; the tungsten paste includes tungsten powder, glass powder and organic carrier in a mass ratio of 88:4.5:11.
[0058] The composite electrode sheet blank is combined with eight second sheet blanks; the temperature during the warm isostatic pressing process is 9.5 MPa, 95°C, and held for 58 min. A mixture of nitrogen and hydrogen is introduced; the hydrogen flow rate is 4.1 L / min and the nitrogen flow rate is 5.3 L / min; the hydrogen is wet hydrogen with a dew point temperature of 38℃. The electrostatic chuck was heated from room temperature to 118°C at a heating rate of 1.8°C / min. The temperature was increased from 118-120℃ to 258℃ at a rate of 0.48℃ / min; from 258℃... The temperature was raised to 718℃ at a rate of 0.18℃ / min. Incubate at 718℃ for 9.5 hours; The temperature was raised to 1210℃ at a rate of 1.9℃ / min; and held at 1210℃ for 140 min. The temperature was increased from 1210℃ to 1578℃ at a rate of 2.59℃ / min; and held at 1578℃ for 148 min. Then, cooling is performed, and the cooling process includes: The temperature dropped from 1578℃ to 1310℃ at a rate of -3.8℃ / min. Replace the introduced hydrogen with dry hydrogen, then cool from 1350-1300℃ to 500-600℃ at a rate of -4 to -5℃ / min; cool from 500-600℃ to room temperature along with the furnace.
[0059] The prepared electrostatic chuck uses alumina ceramic with a surface roughness Ra of 0.18 μm, free from delamination and microcrack defects, and has a dielectric constant of 14.6 and a volume resistivity of 5*10. 14 Ω·cm, flexural strength is 578 MPa.
[0060] Example 3: The contents that are the same as in Example 1 will not be repeated here; this embodiment is different from Example 1. The same scheme is as follows: A method for preparing alumina ceramic for electrostatic chucks further includes placing the composite electrode sheet blank in an environment with a humidity of 38% and letting it stand for 30-60 minutes, and then stacking and warm pressing it with several second sheet blanks.
[0061] The composite electrode sheet blank and several second sheet blanks are laminated and warm-pressed in a mold.
[0062] The technical solution, different from Example 1, further includes: adding MgO powder, Y2O3 powder, TiO2 powder, SiO2 powder, SiC powder, and ZrO2 powder into a ball mill at a mass ratio of 1.5:0.4:0.4:1.2:0.8:0.8, and mixing them in the ball mill to obtain the mixed additive powder. The mass ratio of α-Al2O3 powder to the mixed additive powder is 96:4.
[0063] The process of preparing the first coated material grinding balls also includes the following steps: The polyvinylpyrrolidone was added to a ball mill for grinding, and the grinding process was carried out. The material temperature rose to 132℃; Then add α-Al2O3 powder and grind at room temperature for 40 minutes; Then, while grinding, heat the material and raise the temperature to 132℃ at a rate of 2.2℃ / min. Grind the material at 132℃ for 12 minutes. The grinding ball has a diameter of 1.2 mm, and the volume ratio of the grinding ball to nano-alumina is 2.5:1.
[0064] The process of preparing the second-attached material grinding balls includes the following steps: The mixed additive powder, polyethylene glycol, and the first adhering material grinding balls are placed in a ball mill while the temperature is increased to 65°C. After ball milling at 65℃ for 12 minutes, the mixture was cooled to room temperature to obtain the second deposit. Grinding balls for materials.
[0065] The process of removing the material adhering to the second-attached grinding ball from the grinding ball includes: The following steps: The second type of adhering material grinding balls are placed in a ball mill, and the mill is heated while grinding. Heat to 252℃; grind at 252℃ for 12 minutes; Then, while ball milling, the temperature is lowered, and grinding continues for 12 minutes after the temperature is lowered to room temperature. The alumina powder and inorganic powder attached to the grinding balls detach from the grinding balls, resulting in a mixture. The particle size of the second mixture is D50 = 3.5 μm.
[0066] The toluene, isopropanol, dibutyl phthalate, polyethylene glycol, and polyvinyl alcohol mentioned above. The mass ratio of butyral is 62:22:22:6:22:2; The mass ratio of the first mixed solution to the mixed raw materials is 1.9:1.
[0067] The mixed raw materials are added to the first mixed solution and stirred for 2.6 hours, then allowed to stand for 5.6 hours, and then stirred again for 0.6 hours to obtain the primary slurry.
[0068] The primary slurry was added to a ball mill and ball-milled for 22 hours, then filtered. The mesh count is 260. The filtered primary slurry is fed into a degassing device using nitrogen gas to process the primary slurry. Heating to 86℃ while simultaneously applying a vacuum, the slurry is obtained when the viscosity reaches 3 Pa·s.
[0069] The temperature of the casting slurry is 166℃ when it is cast through the casting equipment. The casting speed is 50 mm / min, and the scraper moves away from the casting belt of the conveying sheet blank during the casting process. The height is 28mm.
[0070] The upper surface of the first sheet blank is heated, and during the heating process, the first sheet blank is heated. The lower surface of the blank is kept warm. The heating temperature is 86°C. After heating for 18 minutes, the first layer blank for screen printing is obtained. Each screen printing layer is 11mm thick, followed by drying at 65℃. The drying time is 19 minutes, and the next screen printing is performed after drying; the tungsten paste includes tungsten powder, glass powder and organic carrier in a mass ratio of 86:2:7.
[0071] The composite electrode sheet blank is combined with 6 second sheet blanks; the temperature during the warm isostatic pressing process is 6 MPa, 86°C, and held for 52 min. A mixture of nitrogen and hydrogen is introduced; the hydrogen flow rate is 3.9 L / min and the nitrogen flow rate is 4.6 L / min; the hydrogen is wet hydrogen with a dew point temperature of 32℃. The electrostatic chuck was heated from room temperature to 112°C using an alumina ceramic preform at a heating rate of 1.2°C / min. The temperature was increased from 112℃ to 252℃ at a rate of 0.35℃ / min; the temperature was increased from 252℃... The temperature was raised to 702℃ at a rate of 0.12℃ / min; and held at 702℃ for 8.5 hours. The temperature was raised to 1205℃ at a rate of 1.6℃ / min; and held at 1205℃ for 125 min. The temperature was increased from 1205℃ to 1565℃ at a rate of 2.6℃ / min; and then held at 1565℃ for 125 min. Then, cooling is performed, and the cooling process includes: The temperature was lowered from 1565℃ to 1310℃ at a rate of -3.2℃ / min; hydrogen was introduced. The gas was replaced with dry hydrogen, and then the temperature was reduced from 1310℃ to 510℃ at a rate of -4.3℃ / min; the temperature was then reduced from 510℃ to room temperature along with the furnace.
[0072] The prepared electrostatic chuck uses alumina ceramic with a surface roughness Ra of 0.17 μm, free from delamination and microcrack defects, and has a dielectric constant of 16 and a volume resistivity of 1*10. 16 Ω·cm, flexural strength is 589 MPa.
[0073] The above description is merely a preferred embodiment of this application and an explanation of the technical principles employed. Those skilled in the art should understand that the scope of the invention involved in this application is not limited to the technical solutions formed by specific combinations of the above-described technical features, but should also cover other technical solutions formed by arbitrary combinations of the above-described technical features or their equivalents without departing from the inventive concept. For example, the above-described features have similar functions to (but are not limited to) those disclosed in this application.
Claims
1. A method for preparing alumina ceramic for electrostatic chucks, characterized in that, Includes the following steps: Preparation of mixed additive powder; The additive powders include MgO powder, Y2O3 powder, TiO2 powder, SiO2 powder, SiC powder, and ZrO2 powder; Mixed additive powder is mixed with fine-grained α-Al2O3 powder to prepare mixed raw materials; Prepare the first mixed solution; Then, the binder and mixed raw materials are added to the first mixed solution to prepare the primary slurry; The primary slurry is degassed to obtain a casting slurry; The casting slurry is cast to obtain a sheet preform; the sheet preform includes... The first layer of blank and several second layer blanks; After preprocessing the first sheet blank, the first sheet blank for screen printing is obtained. body; An electrode layer is attached to the surface of the first sheet blank for screen printing using screen printing paste. A composite electrode sheet preform was obtained; The composite electrode sheet blank and several second sheet blanks are laminated and hot-pressed. The process involves molding to obtain an alumina ceramic blank for an electrostatic chuck. The alumina ceramic blank for electrostatic chucks is debinded and sintered to obtain the alumina ceramic for electrostatic chucks.
2. The method for preparing alumina ceramic for electrostatic chucks according to claim 1, characterized in that, The process of preparing mixed additive powder includes the following steps: MgO powder, Y2O3 powder, TiO2 powder, SiO2 powder, SiC powder, and ZrO2 powder are added to a ball mill in a mass ratio of (1-3):(0.2-1):(0.2-1):(1-2):(0.5-2):(0.5-2) and mixed in the ball mill to obtain the mixed additive powder. The particle size of the mixed additive powder is 0.5-1μm.
3. The method for preparing alumina ceramic for electrostatic chucks according to claim 1, characterized in that, The mass ratio of α-Al2O3 powder to mixed additive powder is (95-99):(3.4-11). The α-Al2O3 powder has a particle size of 0.5-1 μm.
4. The method for preparing alumina ceramic for electrostatic chucks according to claim 1, characterized in that, The process of preparing the mixed raw materials includes the following steps: α-Al2O3 powder and polyvinylpyrrolidone are mixed in a ball mill to prepare a first-attached material grinding ball, which is coated with α-Al2O3 powder. Mixing the mixed additive powder and the first attached material grinding balls in a ball mill to prepare the second attached material grinding balls, which are coated with α-Al2O3 powder and mixed additive powder; The material attached to the second grinding ball is detached from the grinding ball, and then ground. The mixed raw materials are obtained.
5. Preparation of alumina ceramic for electrostatic chucks according to claim 4 The method, characterized in that, The process of preparing the first coated material grinding balls also includes the following steps: The polyvinylpyrrolidone was added to a ball mill for grinding, and the grinding process was carried out. The material temperature rises to 130-150℃; Then, while grinding, the temperature is lowered to room temperature, and polyvinylpyrrolidone is applied to the surface of the grinding ball; Then add α-Al2O3 powder and grind at room temperature for 10-50 min; Then, while grinding, heat the material to 130-135℃ at a rate of 2-5℃ / min, and grind it at 130-135℃ for 10-20 minutes. Then, while grinding, the temperature is lowered until the first attached material grinding ball is obtained after cooling to room temperature. Preferably, the diameter of the grinding ball is 1.0-2.0 mm, and the volume ratio of the grinding ball to the α-Al2O3 powder is (2-4):
1.
6. The method for preparing alumina ceramic for electrostatic chucks according to claim 4, Its features are, The process of preparing the second-attached material grinding balls includes the following steps: The mixed additive powder, polyethylene glycol, and the first adhering material grinding balls are placed in a ball mill, and the temperature is increased while the ball mill is being milled, raising the material temperature to 64-68℃. After ball milling at 64-68℃ for 10-20 minutes, the mixture is cooled to room temperature to obtain... Second attached material grinding balls. and / or The process of removing the material adhering to the second-attached grinding ball from the grinding ball includes: The following steps: The second type of adhering material grinding balls are placed in a ball mill, and the mill is heated while grinding. Heat to 250-260℃; grind at 250-260℃ for 10-20 minutes; Then, while ball milling, the temperature is reduced, and grinding continues for 10-20 minutes after the temperature is reduced to room temperature. The alumina powder and inorganic powder attached to the grinding balls detach from the grinding balls, resulting in a mixture. and / or The particle size of the second mixture is D50 = 3.0-5.0 μm.
7. The method for preparing alumina ceramic for electrostatic chucks according to claim 1, Its features are, The process of preparing the first mixed solution includes: Mix toluene and isopropanol and stir. Then add dibutyl phthalate, polyethylene glycol, and polyvinyl butyral and continue stirring to obtain the first mixed solution; and / or The process of preparing the primary slurry includes: The mixed raw materials are added to the first mixed solution and stirred for 2.5-3.0 hours, then allowed to stand for 5.5-6.0 hours, and then stirred again for 0.5-1.5 hours to obtain the primary slurry. and / or The toluene, isopropanol, dibutyl phthalate, polyethylene glycol, and polyvinyl alcohol mentioned above. The mass ratio of butyral is (60-70):(20-30):(5-10):(20-30):(1-10); The mass ratio of the first mixed solution to the mixed raw materials is (1.8-2.5):
1.
8. The method for preparing alumina ceramic for electrostatic chucks according to claim 1, wherein... The characteristic is that the process of degassing the primary slurry to obtain the casting slurry includes the following steps: The primary slurry is added to a ball mill and milled for 20-25 hours, then filtered with a filter screen of 250-400 mesh. The filtered primary slurry is fed into a degassing device using nitrogen gas to process the primary slurry. Heating to 85-95℃ while simultaneously applying a vacuum, the slurry is obtained when the viscosity reaches 2-6 Pa·s.
9. The method for preparing alumina ceramic for fine electrostatic chucks according to claim 1, characterized in that, The process of casting a film from a slurry to obtain a sheet preform includes the following steps: The temperature of the casting slurry is 165-175℃ when it is cast through the casting equipment. The casting speed is 10-300 mm / min, and the scraper is kept away from the conveying sheet blank during the casting process. The height of the cast strip is 10-30mm; and / or The pretreatment process of the first sheet blank includes the following steps: The upper surface of the first sheet blank is heated, and during the heating process, the first sheet blank is heated. The lower surface of the blank is kept warm. The heating temperature is 85-95℃. After heating for 15-30 minutes, the first layer blank for screen printing is obtained. and / or The electrode layer is attached to the surface of the first sheet blank for screen printing using screen printing paste. The process includes the following steps: The tungsten paste is repeatedly screen-printed onto the surface of the first sheet blank for screen printing. A composite electrode sheet preform was obtained; Each screen printing layer is 10-15mm thick, followed by drying at 60°C. Dry at 80℃ for 15-20 minutes, then proceed with the next screen printing.
10. The method for preparing alumina ceramic for electrostatic chucks according to claim 1, characterized in that, The pressure during the warm isostatic pressing process is 5-10 MPa, the temperature is 85-100℃, and the holding time is 50-60 min. The debinding and sintering process of the alumina ceramic blank for electrostatic chucks includes the following steps. Suddenly: Debinding and sintering are carried out under a nitrogen and hydrogen atmosphere; a mixture of nitrogen and hydrogen gas is introduced; the hydrogen flow rate is 3.8-4.2 L / min, and the nitrogen flow rate is 4.5-5.5 L / min; the hydrogen is wet hydrogen with a dew point temperature of 30-40℃; The electrostatic chuck is placed on a flat and smooth alumina sintering plate and then placed in an integrated debinding and sintering furnace. The temperature is raised from room temperature to 110-120℃ at a rate of 1-2℃ / min. The temperature is increased from 110-120℃ to 250-260℃ at a rate of 0.3-0.5℃ / min; The temperature is increased from 250-260℃ to 700-720℃ at a rate of 0.1-0.2℃ / min; then held at 700-720℃ for 8-10 hours. The temperature is raised to 1200-1220℃ at a rate of 1.5-2.0℃ / min; at 1200-1220℃ Hold at this temperature for 120-150 minutes; raise the temperature from 1200-1220℃ to 1560-1580℃ at a rate of 2.5-3.0℃ / min; and hold at 1560-1580℃ for 120-150 minutes. and / or Then, cooling is performed, and the cooling process includes: The temperature is reduced from 1560-1580℃ to 1350-1300℃ at a rate of -3 to -4℃ / min. Replace the introduced hydrogen with dry hydrogen, and then cool from 1350-1300℃ to 500-600℃ at a cooling rate of -4.5 to -5.5℃ / min; cool from 500-600℃ to room temperature along with the furnace.